Modified toothpaste application using prepared toothpaste delivering technique increases interproximal fluoride toothpaste delivery - Ryouichi Satou; Seitaro Suzuki; Atsushi Takayanagi; Atsushi Yamagishi; Naoki Sugihara (Wiley, 2020)
Abstract Objectives We devised a "prepared toothpaste delivering technique" (PTD technique), a modified the application of toothpaste method for using fluoride toothpaste more effectively. This study aimed to investigate the change in viscosity and fluoride intake into hydroxyapatite of a toothpaste, and deliverability of fluoride toothpaste to the interproximal site with the PTD technique using an interproximal model. Methods Eight toothpaste samples were prepared at the following concentrations: ×1.00, ×1.25, ×1.50, ×1.75, ×2.00, ×3.00, ×4.00, and ×5.00. Viscosity of the toothpaste was measured by a Type‐B viscometer. Dissolution rate of toothpaste and fluoride uptake into the hydroxy apatite pellet were analyzed by a fluoride selective electrode. Application paste volume and delivery rate was measured using interproximal model and image analysis software during using a finger brush front (FBF), finger brush back (FBB), and toothbrush. Results As the dilution ratio increased, the viscosity of the toothpaste decreased sharply, F uptake decreased, and dissolution rate increased. F uptake was significantly reduced when the toothpaste was diluted more than 1.75 times. Therefore, in order to improve the effectiveness of the fluoride toothpaste, it is important to deliver the toothpaste to interproximal areas and pit clefts at low dilution. It was observed that PTD technique can be effectively implemented by the finger brush. Conclusions The use of a FBF surface in the analysis of an acrylic interproximal model could aid in applying pressure while blocking the space of the groove and preventing outflow of the toothpaste. It was considered that the PTD technique would improve the effects of the fluoride toothpaste, especially in the interproximal site.